Kebijakan Jaminan Sosial Kepada Pekerja Migran Indonesia (PMI) Oleh Balai Perlindungan Pekerja Migran Indonesia (BP3MI) - Berlianti Berlianti; Sutriwani Hulu; Indah Lestari Sihombing; Enjelina Simbolon (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Based on BPK regulation No. 6 of 2022 states that the Indonesian Migrant Workers Protection Center (BP3MI) is a Technical Implementation Unit (UPT) under the Indonesian Migrant Workers Protection Agency (BP2MI). BP3MI has the task of implementing Indonesian migrant placement services in accordance with statutory provisions as stated in Law No.18 of 2017. In Medan City itself, there is an office of BP3MI which aims to provide services to every community who becomes an Indonesian Migrant Worker (PMI) and provide insurance in the form of BPJS to PMI so that PMI will feel safe when becoming PMI abroad. In the process, of course, there are several obstacles experienced by PMI such as claiming social security insurance in the form of BPJS that does not meet the requirements. So that the need for strict supervision from BP3MI, so that it can be claimed safely without causing problems.